KEPRAKTISAN ENSIKLOPEDIA FAMILI RUTACEAE DI KEBUN RAYA BANUA UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Masrurah, Elva; Kaspul, Kaspul; Zaini, Muhammad (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
Education is an effort to develop individual abilities and character through various processes such as guidance, teaching, training, and interaction with the environment. 21st century learning emphasizes critical thinking skills and environmental approaches related to the phrases think globally and act locally through the development of encyclopedias at Kebun Raya Banua. An encyclopedia is a type of learning resource that contains descriptions containing knowledge and is arranged (alphabetically) or according to the scientific environment by collaborating on text and images. This study aims to describe the practicality of the Rutaceae family encyclopedia at Kebun Raya Banua. The research method used is the EDR (Educational Design Research) method with Tessmer's formative evaluation design. The one-to-one test subjects were three students and the small group test subjects were four students. The object of this research is the encyclopedia of the Rutaceae family. The results of the study show that the practicality of the content is categorized as good and the practicality of expectations is categorized as very good. This shows that the encyclopedia of the rutaceae family at Kebun Raya Banua is as expected interesting and easy to use to train students' critical thinking skills (practical). Kata kunci: ensiklopedia, famili rutaceae, kepraktisan, penelitian pengembangan